Regulation of the serotonin transporter in the pathogenesis of irritable bowel syndrome - Jin, Duo-Chen; Cao, Hai-Long; Xu, Meng-Que; Wang, Si-Nan; Wang, Yu-Ming; Yan, Fang; Wang, Bang-Mao (World journal of gastroenterology : WJG, 2016)
Serotonin(5-HT) and the serotonin transporter(SERT) have earned a tremendous amount of attention regarding the pathogenesis of irritable bowel syndrome(IBS). Considering that enteric 5-HT is responsible for the secretion, motility and perception of the bowel, the involvement of altered enteric 5-HT metabolism in the pathogenesis of IBS has been elucidated. Higher 5-HT availability is commonly associated with depressed SERT mR NA in patients with IBS compared with healthy controls. The expression difference of SERT between IBS patients and healthy controls might suggest that SERT plays an essential role in IBS pathogenesis, and SERT was expected to be a novel therapeutic target for IBS. Progress in this area has begun to illuminate the complex regulatory mechanisms of SERT in the etiology of IBS. In this article, current insights regarding the regulation of SERT in IBS are provided, including aspects of SERT gene polymorphisms, microR NAs, immunity and inflammation, gut microbiota, growth factors, among others. Potential SERT-directed therapies for IBS are also described. The potential regulators of SERT are of clinical importance and are important for better understanding IBS pathophysiology and therapeutic strategies.